Lithium Polysulfide Interaction with Group III Atoms-Doped Graphene: A Computational Insight - Mauro Francesco Sgroi; Daniele Pullini; Alina Iuliana Pruna (Batteries, 2020)
The development of long lifetime Li–S batteries requires new sulfur–carbon based composite materials that are able to suppress the shuttle effect—namely, the migration of soluble lithium polysulfides from the cathode to the anode of the cell. Graphene is one of the most promising carbon supports for sulfur, thanks to its excellent conductivity and to the possibility of tailoring its chemical–physical properties, introducing heteroatoms in its structure. By using first principle density functional theory simulations, this work aims at studying the effect of doping graphene with group III elements (B, Al, Ga) on its electronic properties and on its chemical affinity towards lithium polysulfides. Our results show that Al and Ga doping strongly modify the local structure of the lattice near heteroatom site and generate a charge transfer between the dopant and its nearest neighbor carbon atoms. This effect makes the substrate more polar and greatly enhances the adsorption energy of polysulfides. Our results suggest that Al- and Ga-doped graphene could be used to prepare cathodes for Li–S cells with improved performances and lifetime.